2021
DOI: 10.21608/ejhc.2021.198467
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Communication Skills Training Program for Head Nurses on Interpersonal Relations and Nurses' Organizational Commitment

Abstract: Background: Nurses are the most precious assets of any health-care institution, thus it's critical to understand their behavior. In this regard, the present study was carried out in order to examine the effect of communication skills training program for head nurses on interpersonal relations and nurses' organizational commitment. This study was carried out at Zagazig University Hospitals, using quasi experimental design. A convenience sample of 50 head nurses and simple random sample of 221 staff nurse from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Several research studies have confirmed the beneficial impact of FLNMs' communication skills and abilities on the performance and satisfaction of nurses. As noted by Abd El-Fattah Mohamed et al (7) and Abdeen et al (8), the communication skills and proficiency of FLNMs influences the satisfaction and commitment. Also agreed with, Ghazawy et al (9), discovered that over half of nurses demonstrate a strong commitment to their duties.…”
Section: Introductionmentioning
confidence: 89%
“…Several research studies have confirmed the beneficial impact of FLNMs' communication skills and abilities on the performance and satisfaction of nurses. As noted by Abd El-Fattah Mohamed et al (7) and Abdeen et al (8), the communication skills and proficiency of FLNMs influences the satisfaction and commitment. Also agreed with, Ghazawy et al (9), discovered that over half of nurses demonstrate a strong commitment to their duties.…”
Section: Introductionmentioning
confidence: 89%